A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae) - Ribera, Carles (Zootaxa, 2018)
This paper describes a new genus of Nesticidae based on morphology of the genital characters and supported by molecular data. The new genus, Domitius n. gen., includes a group of seven cave-dweller species spread along western European peninsulas (Iberian and Italian). Molecular phylogenetic analysis shows that these species constitute an independent and highly supported evolutionary lineage being the sister group to Kryptonesticus Pavlek & Ribera, 2017, Nesticus Thorell, 1869 and Carpathonesticus Lehtinen & Saaristo, 1980 genera. As a result, seven new combinations are here proposed: Domitius baeticus (López-Pancorbo & Ribera, 2011) n. comb., Domitius murgis (Ribera & De Mas, 2003) n. comb., Domitius lusitanicus (Fage, 1931) n. comb., Domitius luquei (Ribera & Guerao, 1995) n. comb., Domitius sbordonii (Brignoli, 1979) n. comb., Domitius menozzii (Caporiacco, 1934) n. comb., Domitius speluncarum (Pavesi, 1873) n. comb.